Challenges of Performance-Based Payment Methods in Health Care System: A Systematic Review - Seyed Mehdi Paknejad Rizi; Fatemeh Torabi; Hamideh Jafari Pavarsi (Shahid Sadoughi University of Medical Sciences, 2022)
Background: Performance-based payment refers to an incentive-based payment to employees in terms of and beyond their job requirements at an extremely high quality. Therefore, this study aims to review the challenges of performance-based payment in the healthcare system. Methods: The study was carried out as a systematic review through searching databases, i.e., PubMed, Web of Science, and Scopus, for articles published without time limitation to September 30, 2020. The research articles regarding Performance-based payment in hospitals (n = 16) were examined. Results: Generally, challenges of performance-based payment were divided into four main categories and 17 subcategories, including service providers, payment and financing, quality of provided services, and infrastructure. The main themes and sub-themes were related to the lack of financial resources, discrimination between patients, and the designing of a comprehensive information system. Conclusion: Suitable implementation of performance-based payment methods in the healthcare system will improve quantitative and qualitative indicators of staff performance. Identifying the challenges and obstacles to the proper implementation of this plan will help health managers and policymakers design and implement remedial measures. It is to reduce the barriers and problems.